The Moderating Role of Self-Esteem in the Relationship Between Organisational Climate and Humiliation at Work. A Multi-Group SEM Analysis - Żenda, Aleksandra; Kożusznik, Barbara; Paliga, Mateusz; Blukacz, Mateusz (Przegląd Psychologiczny, 2025)
Purpose: The study examined how the dimensions of organizational climate and humiliation at work are related and whether an individual's self-esteem moderates this relationship to see if self-esteem is a buffer against adverse work situations. Methodology: There were 672 contract employees who completed questionnaires through a research panel. In this cross-sectional study, three measures were used Organisational Climate Questionnaire, Humiliation Inventory and the Self-liking and Sense of Competence Scale. Findings: The study found that organizational climate correlates positively with employees’ negative experiences. The study results revealed that it was mainly problems with co-workers and work organization that predicted experiences of humiliation at work, while difficult relationships with superiors translated into feelings of humiliation only in those with low self-esteem. In addition, the study examined the role of self-esteem in buffering stress and difficult emotions at work and found that while there was a positive correlation between organizational climate and self-esteem, there was no overall buffering effect of self-esteem on the relationship between organizational climate and humiliation at work. Conclusions: Developing self-esteem among employees is important because it can lead to increased creativity, productivity, and job satisfaction. However, this study goes beyond the buffering role of self-esteem and shows that high self-esteem can also contribute to difficult states, such as humiliation. Given the cross-sectional nature of this study, the conclusions should be interpreted within the limits of its design and are offered primarily from a theoretical standpoint. Nevertheless, this work is one of the few to address the topic of humiliation at work and its organizational correlates, and corresponds with theories that shed light on optimal versus high levels of self-esteem.